Bacteroides Fragilis Exacerbates T2D Vascular Calcification by Secreting Extracellular Vesicles to Induce M2 Macrophages - Cong Chen; Zhengfeng Liang; Yuqi He; Yan Gao; Shuhui Ouyang; Lili Wang; Jianghua Liu; Jingsong Cao (Advanced Science)
Abstract Vascular calcification (VC) in type 2 diabetes (T2D) poses a serious threat to the life and health of patients. However, its pathogenesis remains unclear, resulting in a lack of effective treatment for the root cause. It is found that both intestinal Bacteroides fragilis (BF) and peripheral M2 monocytes/macrophages are significantly elevated in patients with T2D VC. M2 macrophages are identified as a significant risk factor for T2D VC. Both BF and their extracellular vesicles (EV) promote T2D VC and facilitate macrophage M2 polarization. Macrophages clearance significantly antagonized BF EV‐induced T2D VC in mice. Mechanistically, EV‐rich double‐stranded DNA (dsDNA) activates stimulator of interferon response cGAMP interactor 1 (Sting), promotes myocyte enhancer factor 2D (Mef2d) phosphorylation, upregulates tribbles pseudokinase 1 (Trib1) expression, and induces macrophage M2 polarization. Concurrently, Mef2d activated by the EV targets and upregulates the expression of pro‐calcification factor Serpine1, thereby exacerbating T2D VC. Clinical studies have shown that Serpine1 is significantly elevated in the peripheral blood of patients with T2D VC and is closely associated with T2D VC. In summary, this study reveals that intestinal BF promotes Trib1 expression through the EV‐Sting‐Mef2d pathway to induce macrophage M2 polarization and upregulates serpin family E member 1 (Serpine1) expression, thereby aggravating T2D VC. The findings provide a new theoretical and experimental bases for optimizing the strategies for prevention and treatment of T2D VC.